Peran Diagnosis Dini dan Pendekatan Terapi Individual pada Obstructive Sleep Apnea Dewasa - Rachel Agustin Inggrid Zefanya; Mukhlis Imanto (CV. Jasa Sukses Abadi, 2026)
Obstructive Sleep Apnea (OSA) is a sleep-related breathing disorder characterized by recurrent upper airway obstruction, leading to intermittent hypoxemia and sleep fragmentation. In adults, OSA is frequently underdiagnosed due to nonspecific symptoms, resulting in an increased risk of cardiovascular and metabolic complications as well as reduced quality of life. Early diagnosis plays a crucial role in preventing disease progression and long-term complications. This article aims to review the role of early diagnosis and the importance of individualized therapeutic approaches in adult patients with OSA based on current literature. This study was conducted as a literature review of scientific publications discussing the pathophysiology, clinical manifestations, diagnostic methods, and management of adult OSA. Diagnosis of OSA requires a comprehensive approach, including clinical history, physical examination, screening tools, and confirmation through polysomnography. Management of adult OSA should be individualized, taking into account disease severity assessed by the apnea–hypopnea index (AHI), upper airway anatomical characteristics, body mass index, presence of comorbidities, as well as patient tolerance and adherence to therapy. Continuous Positive Airway Pressure (CPAP) remains the first-line treatment for moderate to severe OSA, while lifestyle modification, oral appliances, and surgical interventions may be considered in selected cases. In conclusion, the combination of early diagnosis and individualized therapeutic strategies is essential for optimal management of adult OSA, contributing to improved clinical outcomes and patient quality of life.